Patenting for profitability: green energy innovations and firm performance in BRICS countries - Makeeva, Elena; Popov, Konstantin; Teplova, Olga (Frontiers in Environmental Science, 2024)
Introduction: Despite the significant advancements in renewable energy technologies, the current energy system remains heavily reliant on fossil fuels. However, an increasing number of studies have demonstrated that the proliferation of "green" patents is contributing to the transition towards a more sustainable energy future, with important implications for both environmental sustainability and corporate financial performance.Methods: Utilizing panel data sourced from 63 of the most prominent energy sector companies within the BRICS countries during the period between 2011 and 2020, we conducted a comprehensive analysis with the objective of uncovering the distinct impacts of various types of patents in renewable energy technologies on the firm's financial performance indicators (ROA, ROIC, and market capitalization) by using multiple regression modeling.The FGLS estimations reveal that higher CO2 emissions correlate with lower ROA, ROIC, and market capitalization of energy companies, significant at the 5% level. Additionally, while renewable energy technologies (Y02E10) did not impact ROA, they contributed significantly to ROIC at the 1% level. Combustion technologies with mitigation potential (Y02E20) positively influence all financial performance indicators, and nuclear energy technologies (Y02E30) significantly contribute to both ROA and ROIC at the 10% level.Discussion: Our research demonstrates that technological advancements in national economies are not consistent and that disparities exist in specific data segments. Advancements are observed in certain areas, highlighting the significance of national legislation in promoting green finance and renewable energy development. This emphasizes the need for BRICS countries to prioritize renewable energy technologies and adopt legislative initiatives from developed nations as a model for achieving clean technological growth and renewable energy targets.